2017
DOI: 10.2174/1874325001711010934
|View full text |Cite
|
Sign up to set email alerts
|

Management of Glenoid Defects in Anterior Shoulder Instability: A Review of Current Concepts

Abstract: Background:Bone defects of the glenoid are often found in patients with traumatic anterior glenohumeral instability. There is no consensus regarding which glenoid defects need to be treated surgically. The aim of this review is to describe the management of glenoid defects in anterior shoulder instability in patients with traumatic anterior glenohumeral instability.Methods:We conducted a review of the literature through a Pubmed search.Results:The management of glenoid defects in anterior shoulder instability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…10,15,19 Shaha and colleagues 24 reported that 13.5% glenoid bone loss was associated with poor outcomes in patients who underwent isolated arthroscopic labral repair. They measured bone loss using magnetic resonance imaging with the perfect circle technique described by Harmsen and Huijsmans, 13 and patients were divided into quartiles based on the percentage of bone loss. They arbitrarily set the subcritical threshold cutoff at 13.5%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,15,19 Shaha and colleagues 24 reported that 13.5% glenoid bone loss was associated with poor outcomes in patients who underwent isolated arthroscopic labral repair. They measured bone loss using magnetic resonance imaging with the perfect circle technique described by Harmsen and Huijsmans, 13 and patients were divided into quartiles based on the percentage of bone loss. They arbitrarily set the subcritical threshold cutoff at 13.5%.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Although Bankart repair is an effective method for addressing recurrent anterior shoulder instability, recent studies have demonstrated that failure to address glenoid bone loss is a common cause of recurrent instability after isolated Bankart repair. 4,10,13,17,25,26 In contrast to subcritical bone loss, multiple studies have defined critical bone loss of the anterior glenoid associated with recurrent anterior shoulder instability after Bankart repair, with percentages reported ranging from 15% to 30%. 9,11 Several open and arthroscopic operative techniques are utilized to reconstruct the glenoid with a variety of autograft and allograft sources.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,10 Various glenoid reconstruction procedures that were designed to address the bone loss have been described, and they include the Latarjet procedure, arthroscopic iliac crest bone graft augmentation, and free bone block transfers. 8,18 The Latarjet procedure has shown good to excellent clinical outcomes in terms of recurrence of stability and is the current gold standard for the management of glenoid bone loss; however, a concern with this procedure is an underappreciated complication rate, reported between 15% and 30%, which includes serious neurovascular injuries, difficulties in revision, chances of long-term progression to glenohumeral arthritis (attributed to the nonanatomic reconstruction technique), and graft resorption. 7,16,18 To avoid serious neurovascular injuries, an arthroscopic anatomic glenoid reconstruction (AAGR) technique using a frozen distal tibial allograft (DTA) with patients in the lateral decubitus position was developed.…”
mentioning
confidence: 99%
“…The second part is focused in anterior instability with four reviews of the natural history [ 9 ], management alternatives of bone defects [ 10 , 11 ] and soft tissues [ 12 ] in instability and a fifth over the failed shoulder instability patient [ 13 ]. Three “controversies” papers focus in specially disputed topics: management of the first shoulder dislocation [ 14 ], open or arthroscopic procedures [ 15 ] and associated procedures during Bankart repair [ 16 ].…”
mentioning
confidence: 99%